Perspektif Komunikasi dalam Pengembangan Organisasi - Andrifan Dwi Prabowo; ika r. daya; surya darma; Dedi Sahputra (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2021)
This study aims to determine the perspective of communication in organizational development. This research discusses organizational development from a communication point of view. This research uses a literature study approach. The results of this study are coordination between individuals and between departments in organizational development requires effective communication so that the message or information conveyed by the managerial has been received by the subordinates, and there has been an understanding between the managerial and subordinates about the goals desired by the managerial and then the subordinates give feedback as expected by the manager